Strategic Defense HRM 4.0: An Integrative Framework for Future-Ready Defense Organizations - Hengky T. P. Aritonang; Guntur Eko Saputro; Imam Tri Wahyudi (Jurnal Manajemen Universitas Bung Hatta, 2026)
The Fourth Industrial Revolution—artificial intelligence, autonomous systems, and hybrid threats—is fundamentally reshaping defense organizations. Traditional hierarchical personnel systems are increasingly inadequate for preparing military forces to operate across physical, digital, and cognitive domains. Despite this challenge, defense Human Resource Management (HRM) scholarship lacks a comprehensive framework integrating technological transformation, human-machine collaboration, and strategic workforce planning. This systematic review followed PRISMA 2020 guidelines, searching Scopus, Web of Science, and IEEE Xplore (2020–2025). From 512 publications, 52 peer-reviewed studies were thematically synthesized with independent double-coding (κ=0.82). Three key insights emerged: (1) predictive analytics in defense contexts improve personnel retention and enable proactive forecasting of critical skill gaps; (2) immersive VR/AR training enhances skill retention and reduces training duration; (3) ethical human-machine teaming requires explainable AI, calibrated trust, and ethical reasoning-focused leadership. These findings are integrated into the Strategic Defense HRM 4.0 Framework, comprising four pillars: data-driven talent management, digital workforce readiness, ethical human-machine teaming, and strategic HRM for organizational readiness. This framework enables defense organizations to transition from reactive personnel administration to proactive strategic workforce management.